Systematic approaches to dissect biological processes in stem cells by image-based screening - Erdmann, Gerrit; Volz, Hans Christian; Boutros, Michael (Biotechnology journal, 2012)
High-throughput RNAi or small molecule screens have proven to be powerful methodologies for the systematic dissection of cellular processes. In model organisms and cell lines, large-scale screens have identified key components of many cellular pathways and helped to identify novel targets in disease-relevant pathways. Image-based high-content screening has become an increasingly important tool in high-throughput screening, enabling changes in phenotype characteristics, such as cell morphology and cell differentiation, to be monitored. In this review, we discuss the use of image-based screening approaches to explore the behavior of adult, embryonic, and induced pluripotent stem cells. First, we review how current pluripotency and differentiation assays can be adapted to high-throughput formats. We then describe general aspects of image-based screening of cells and present an outlook on challenges for screening stem cells.
Gesehen am 21.11.2018